An elephant in the room: university chaplains cultivating healthy religious diversity through respectful dialogue. Issue 4 (2nd October 2021) - Cronshaw, Darren; Daddow, Newton
ABSTRACT: Finding Common Ground (FCG) is an inter-belief dialogue program hosted in the Multi Faith Facility of Swinburne University of Technology. FCG is a voluntary program that offers Swinburne students a safe space to discuss their religious faith, or alternative value base, and to learn from those of others. Two iterations of this program were evaluated in 2018. We argue that nurturing healthy religious expression and cultivating respect for diverse religious and other belief frameworks is essential in today's multi-religious and pluralist world. Furthermore, we suggest that such exploration in the diverse (secular) university context is addressing something of 'an elephant in the room' in student life and learning in contemporary universities. We also recognise the reality of unhealthy expressions and fundamentalist assertions that fuel wider community aversion to a focus on overt religious conversations that tilt towards controversial debate and polarisation. This article principally analyses the experience of one student participant 'Antoni' to highlight significant themes reflected in the overall student responses: why FCG was a 'safe place' for dialogue, and how it cultivated empathy and humility, inter-faith community and pastoral support, healthy religious outlooks (rather than 'spiritual bypass') and personal formation.